A Study of the Use, Knowledge, and Beliefs About Cigarettes and Alternative Tobacco Products Among Students at One U.S. Medical School. (December 2015) - Zhou, Sherry; Van Devanter, Nancy; Fenstermaker, Michael; Cawkwell, Philip; Sherman, Scott; Weitzman, Michael
Abstract : Purpose: In the United States, the prevalence of the use of alternative tobacco products (ATPs) (e.g., hookahs, e-cigarettes, cigars/cigarillos) has increased sharply. As future health care providers, medical students will play a critical role in health promotion and disease prevention. This study investigated medical students' use, knowledge, and beliefs about cigarettes and ATPs. Method: In 2014, the authors surveyed all students enrolled at one medical school in New York City. The survey included questions about personal use of tobacco products, perceptions about the harms of ATPs and their role in disease causation, education about ATPs, and cessation training and practices related to ATPs and cigarettes. The authors compared results across medical school classes. Results: Of 720 students, 431 (59.9%) completed the survey. Of those, 64 (14.7%) were current users of tobacco or smoking products, including cigarettes (17; 3.9%), ATPs (21; 4.8%), or marijuana (39; 8.9%). Many believed that ATPs contributed less than cigarettes to various diseases. Respondents received less cessation training regarding ATPs than cigarettes ( P < .0001). They felt less confident providing ATP cessation counseling than cigarette cessation counseling ( P < .0001) and were less likely to report counseling patients on ATP cessation than cigarette cessation (46 [10.7%] versus 280 [64.8%], P < .0001). Conclusions: A concerning percentage of surveyed medical students use tobacco products, including ATPs, and lack the knowledge, education, and cessation counseling skills to provide accurate information about them to patients. ATP education should be added to medical school curricula to address this gap.